Heterogeneity along the Height in Disc Specimens of Graphite/Tungsten Powder Mixtures with Sub-Stoichiometric Carbon Atom Ratios Heated by Concentrated Solar Beam to 1600 C - Shohoji, Nobumitsu (2010)
Compositional heterogeneity along the thickness of compacted disc specimens of graphite/tungsten powder mixtures with substoichiometric carbon atom ratios (0.35, 0.50 and 1.00) heated by concentrated solar beam to 1600 C was characterised by X-ray diffraction. Top surface of any examined test piece was consisted purely of mono-carbide WC while the bottom surface showed different constitution depending on the net initial C/W ratio of the test piece; almost pure metallicWfor the C/W ¼ 0:35 specimen, dominant metallicWassociated with small proportion ofW2C for the C/W ¼ 0:50 and dominantW2C with trivial proportion of WC for the C/W ¼ 1:0. In the intermediate zone between the top and the bottom layers, the constitution held virtually constant depending on the nominal C/W ratio of the starting material: co-existing metallicWandW2C for the C/W ¼ 0:35, pureW2C for the C/W ¼ 0:50 and predominant WC with traceW2C for the C/W ¼ 1:00. Unlike for the top surface of the C/W ¼ 0:35 test piece heated in a solar furnace to 1900 C reported earlier, no evidence of formation of nano-meter scale WC whisker was detected for the top surface in any sample heated to 1600 C in the present work.